Identification of Elemental Content and Rock Types in West Lampung Regency - Nadya Fitra Kurnia; Hamdi Rifai; Syafriani Syafriani; Letmi Dwiridal; Fatni Mufit (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
Rock is a constituent of the earth's crust from a collection of minerals that harden due to natural processes. Rocks formed from volcanic eruption materials in each place have different characteristics in distribution patterns, types of minerals and the content of elements contained therein. These rocks contain elements that form magnetic minerals. However, in rocks in West Lampung Regency the elemental content in the rocks has not been identified. This study aims to determine the composition of rock-forming elements and rock types found in West Lampung Regency. The elemental content in rocks can be identified using X- Ray Fluorescence (XRF) and determine rock types using SiO2and K2O diagrams. The results of the analysis using XRF show that Si (Silica) is the most dominant element found in 4 rocks in Lampung Regency. West. In addition, the elements found in rocks in West Lampung are Al, Si, K, Ca, Fe, P, Cl, Ti, Mn, Ni, Cu, Zn, Ga, As, Rb, Sr, Y, Zr, Ag, In, Eu, and Pb , from the content of these elements there are elements that form magnetic minerals, namely Fe and Ti , with rock types of Foidite and Decite.